Effect of Malva Neglecta Wallr on Ethylene Glycol Induced Kidney Stones - Saremi, Jamileh; Kargar-Jahromi, Hossein; Pourahmadi, Mohammad (Urology Journal, 2015)
Purpose: The aim of this study was to investigate the anti-urolithiasis effects of aqueous extracts of Malva neglecta Wallr on ethylene glycol and ammonium chloride induced kidney stones in a rat model. Materials and Methods: A total number of 64 male Wistar rats were randomly divided into eight groups equally: group I (normal control), group II (disease control), groups III and IV (sham), groups V and VI (preventive groups), and groups VII and VIII (curative groups). Group I received tap drinking water, groups III and IV were given intra-peritoneal injections of 200 and 800 mg/kg aqueous extracts for 28 days. Groups II, V, VI, VII, and VIII received 1% ethylene glycol plus 0.25% ammonium chloride in drinking water for 28 days. Groups V and VI were given intra- peritoneal injections of 200 and 800 mg/kg aqueous extracts for 28 days and groups VII and VIII received intra-peritoneal injections of 200 and 800 mg/kg aqueous extracts from the 14th day of the experiment. After 28 days the kidneys were removed and observed for calcium oxalate (CaOx) deposits and tubulointerstitial changes. Results: The extract significantly decreased CaOx deposits and tubulointerstitial damage in the preventive groups (P < .001). In curative groups, a low dosage of extract, reduced kidney oxalate deposits and tubulointerstitial damage (P < .05). In addition a significant decrease was observed in crystal deposition and tubulointerstitial damage in high dosed group (P < .001). However, high dosed preventive and curative groups seemed to be more effective (P ≤ .001). Conclusion: Malva neglecta Wallr has beneficial effects on preventing and treating CaOx deposition and decreasing tubulointerstitial damage on a dosage dependent manner. These effects may be due to the components presented in this plant such as saponins, flavonoids, mucilage, and phenolic compounds.